2005
DOI: 10.1007/s11240-004-1020-x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid micropropagation of Curcuma longa using bud explants pre-cultured in thidiazuron-supplemented liquid medium

Abstract: Multiple shoots of Curcuma longa were induced by culture of bud explants for 1 week in Murashige and Skoog (MS) liquid medium supplemented with 72.64 lM thidiazuron (TDZ) prior to culture on MS gelled medium without growth regulator for 8 weeks. The regeneration rate was up to 11.4 ± 1.7 shoots/explant. Rooting was spontaneous and the regenerated plants were successfully transferred to soil. This protocol can be an alternative for rapid micropropagation of C. longa used for phytomedicine raw material productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
17
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 10 publications
10
17
1
Order By: Relevance
“…The results suggest that a short (6 h) exposure of explants to 25 or 50 lmol L -1 TDZ, prior to the transfer to SH multiplication medium with growth regulators, led to increased shoot proliferation of H. procumbens. Similar stimulating effects of TDZ pretreatment on multiple shoot formation have been previously reported for some other plant species, such as Curcuma longa (Prathanturarug et al 2003(Prathanturarug et al , 2005, Prunus cerasus (Song and Sink 2005), Ocimum basilicum (Siddique and Anis 2007), Rosa spp. (Kucharska and Orlikowska 2009) and Nyctanthes abor-tristis (Jahan et al 2011).…”
Section: Shoot Proliferationsupporting
confidence: 85%
See 1 more Smart Citation
“…The results suggest that a short (6 h) exposure of explants to 25 or 50 lmol L -1 TDZ, prior to the transfer to SH multiplication medium with growth regulators, led to increased shoot proliferation of H. procumbens. Similar stimulating effects of TDZ pretreatment on multiple shoot formation have been previously reported for some other plant species, such as Curcuma longa (Prathanturarug et al 2003(Prathanturarug et al , 2005, Prunus cerasus (Song and Sink 2005), Ocimum basilicum (Siddique and Anis 2007), Rosa spp. (Kucharska and Orlikowska 2009) and Nyctanthes abor-tristis (Jahan et al 2011).…”
Section: Shoot Proliferationsupporting
confidence: 85%
“…The response of the explants in terms of a number of regenerated shoots and their length to different concentrations and duration of TDZ exposure was determined. TDZ (a synthetic phenylurea derivative) is efficient for the formation of adventitious shoots and axillary shoot proliferation, and the technique of explant pretreatment with the growth regulator has been successfully used by several authors for the improvement of in vitro plant micropropagation (Singh and Syamal 2001;Prathanturarug et al 2003Prathanturarug et al , 2005Siddique and Anis 2007;Jahan et al 2011). For example, Jahan et al (2011) used it to micropropagate Nyctanthes arbor-tristis.…”
Section: Introductionmentioning
confidence: 99%
“…A successful regeneration of the subdivided rosettes from TDZ was observed when they were transferred to MS culture media without growth regulators, showing that subcultivation in these conditions is crucial for later development of these explants (Khalafalla and Hattori, 1999;Joshi et al, 2008). Although Prathanturarug et al (2005) has suggest that a second treatment with TDZ may increase culture multiplication, the results from our work do not corroborate with this possibility, since explants regeneration in culture media supplemented with high doses of TDZ was very low. The plantlets regenerated in MS medium presented normal morphology and similarity of plants not subjected to TDZ treatment, a result also found by Siddique and Anis (2007) in Ocimum basilicum L. cultures.…”
Section: Cultured In Vitrocontrasting
confidence: 64%
“…Among the various tested concentrations and culturing durations, the highest shoot regeneration frequency (90%), mean number of shoots (23.1 § 2.15) and maximum shoot length (5.3 § 0.83 cm) were recorded after 8 weeks at 50 mmol/L TDZ for 8 days culture duration (Figure 2(A)). The effectiveness of short term exposure and stimulating effect of TDZ on bud break and multiple shoot formation has been reported earlier for several medicinal and aromatic plant species including Ocimum basilicum, [10] Arachis correntina, [65] Curcuma longa, [66] Curculigo orchioides [67] and Mentha arvensis. [68] It is suggested that TDZ may be needed as a trigger for initiating the proliferation of shoot meristems.…”
Section: Effect Of Tdz Dosage and Duration In Liquid Ms Mediummentioning
confidence: 74%